Estratégias competitivas aplicadas pelos stakeholders construtores - Oliveira, Kaio Pimentel Rego de; Monteiro, Camila de Oliveira; Roriz, Rafaela Franca; Pinto, Maria Gabriela Almeida; Lima, Renan Tenório de Araújo; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Because the high subjectivity of value perception, besides the competitive environment of civil construction market, the focus on the external customer usually conflicts with the value to the organization’s internal customer. Thus, it is questioned who the different stakeholders in the construction chain are, and at what levels should have their view of value considered. As part of this process, this article aims to understand how stakeholders-builders have applied different management strategies in the crowded construction market. For this, semi-structured questionnaires were applied to managers of different companies, especially those with strategic decision-making powers. With this, a characterization of the management profiles was obtained, perceiving similar foci in the strategies of the companies, mainly in relation to the marketing for the external client and the internal innovation. It is concluded that, although there are clear focuses on business strategies, there is significant room for improvement in sectors such as technological innovations, people management and supplies.